Language-specific strategy for programming hearing aids — A double-blind randomized controlled crossover study. Issue 4 (August 2018) - Matsumoto, Nozomu; Suzuki, Nobuyoshi; Iwasaki, Satoshi; Ishikawa, Kazuha; Tsukiji, Hiroki; Higashino, Yoshie; Tabuki, Tomoko; Nakagawa, Takashi
Abstract: Objective: Voice-aligned compression (VAC) is a method used in Oticon's hearing aids to provide more comfortable hearing without sacrificing speech discrimination. The complex, non-linear compression curve for the VAC strategy is designed based on the frequency profile of certain spoken Western languages. We hypothesized that hearing aids could be further customized for Japanese-speaking users by modifying the compression curve using the frequency profile of spoken Japanese. Methods: A double-blind randomized controlled crossover study was performed to determine whether or not Oticon's modified amplification strategy (VAC-J) provides subjectively preferable hearing aids for Japanese-speaking hearing aid users compared to the same company's original amplification strategy (VAC). The participants were randomized to two groups. The VAC-first group received a pair of hearing aids programmed using the VAC strategy and wore them for three weeks, and then received a pair of hearing aids programmed using VAC-J strategy and wore them for three weeks. The VAC-J-first group underwent the same study, but they received hearing aids in the reverse sequence. A Speech, Spatial and Qualities (SSQ) questionnaire was administered before beginning to use the hearing aids, at the end of using the first pair of hearing aids, and at the end of using the second pair of hearing aids. Results: Twenty-five participants that met the inclusion/exclusion criteria from January 1 to October 31, 2016, were randomized to two groups. Twenty-two participants completed the study. There were no statistically significant differences in the increment of SSQ scores between the participants when using the VAC- or the VAC-J-programmed hearing aids. However, participants preferred the VAC-J strategy to the VAC strategy at the end of the study, and this difference was statistically significant. Conclusion: Japanese-speaking hearing aid users preferred using hearing aids that were fitted with the VAC-J strategy. Our results show that the VAC strategy can be adjusted to the frequency profile of different languages and that participants expressed their subjective preference more clearly than was reflected in the SSQ scores. A similar language-specific strategy may improve user's satisfaction while using hearing devices, and this concept may be extended to implantable hearing devices. Clinical research registration number: R000023191.